The Relationship Between Principal Leadership Behavior and Learning Supervision to the Teacher Performance at SMAN 5 Taruna Brawijaya East Java - Efendi, Nur; Sholeh, Muh Ibnu; Andayani, Dwi; Singh, Irom Gambhir; Ayudhya, Panornuang Sudasna Na; Sahri (Migration Letters, 2023)
This research to determine the relationship between school principal leadership behavior on teacher performance, determine the relationship between learning supervision and teacher performance, and determine the collective relationship between school principal leadership behavior and learning supervision on teacher performance. This research method uses a quantitative approach. The population used as focus is all 50 teachers. The sample taken reached 34 respondents from the population. Sample collection was carried out using probability sampling techniques. Data was collected through questionnaires. The questionnaire uses a Likert scale with categories of strongly agree (SS), agree (S), neutral (N), disagree (TS), and strongly disagree (STS). Distribution of questionnaires was carried out via Google Form to respondents online. The collected data was analyzed using descriptive statistical methods and Partial Least Square (PLS). The results of the research show that there is a positive and significant relationship between the principal’s leadership behavior (X1) and teacher performance (Y), there is a positive and significant relationship between learning supervision (X2) and teacher performance (Y), and there is a positive and significant relationship between learning supervision (X2) and teacher performance (Y). collectively significant between the principal’s leadership behavior (X1) and learning supervision (X2) on teacher performance (Y).